Contrasting patterns in trophic niche evolution of polymorphic Arctic charr Salvelinus alpinus L. populations in two subarctic lakes, northern Norway - Moccetti, Paolo Maria (UiT Norges arktiske universitet, 2018)
The trophic niche (recent and time-integrated niche estimates) of polymorphic populations of Arctic charr was investigated in two lakes in Northern Norway. The lakes, Tårnvatn and Skøvatn, have three and two morphs, respectively. Since the two systems are very similar in environmental conditions and fish communities, comparable niches between similar trophic morphs across lakes were expected caused by parallel local evolutionary process. Three methods were used to describe the niches: habitat choice and stomach content to estimate the recent feeding behaviour, and time integrated methods like trophically-transmitted parasite communities and stable isotopes (δ13C and δ15N) as proxies for the long-term trophic niches. The combined data from habitat distribution, stomach contents, parasites, and stable isotopes analyses showed a distinct segregation in stable trophic resource utilization of the different Arctic charr morphs in Skøvatn and Tårnvatn. The trimorphic Tårnvatn has one littoral omnivorous (LO), one small-sized profundal benthivorous (PB), and a large-sized profundal piscivorous (PP) morph foraging on conspecifics (cannibalistic), only reported once in the same region in Norway. In contrast, a novel charr variety was discovered in Skøvatn: a small-sized profundal zooplanktivorous-morph (PZ). Compared to the sympatric LO-morph, the PZ-morph has different stable isotope values and also contrasting parasite communities, including heavy infection by copepod-transmitted Diphyllobothrium-parasites. A rather clear parallelism in habitat choice and external morphology was found between the small-sized deep-water morphs and the upper-water omnivore LO-morphs in the two lakes. This suggested a common parallel evolutionary process along the depth gradient across lakes. However, contrary to the hypotheses, there was an evident non-parallel pattern in diet between the small-sized profundal benthivorous PB-morph and the zooplanktivorous PZ-morph indicating partially different evolutionary histories. These findings show ...